Microbiota-derived short-chain fatty acids: Implications for cardiovascular and metabolic disease - Lu, Yingdong; Zhang, Yang; Zhao, Xin; Shang, Chang; Xiang, Mi; Li, Li; Cui, Xiangning (Frontiers in Cardiovascular Medicine, 2022)
Cardiovascular diseases (CVD) are on the rise around the globe over the past decades despite the existing prevention and treatment guidelines. Short-chain fatty acids (SCFAs), the main metabolites fermented by the specific colonic anaerobic bacteria in the gastrointestinal tract, have been spotted as the critical metabolites in CVD of the host. More accumulating evidence is suggesting that the end products of SCFAs (including acetate, propionate, and butyrate) interact with CVD by maintaining intestinal integrity, anti-inflammation, glucolipid metabolism modulation, and blood pressure and gut-brain axis activation. Recent advances suggest potentially promising path to prevent and treat CVD by controlling SCFAs. Thus, the fundamental purpose of this review is to summarize the various functional roles carried out by the SCFAs that are reported in CVD studies. To provide an outlook, this review highlights the novel therapeutic interventions that target SCFAs to prevent and treat CVD.